2011
DOI: 10.1039/c0lc00612b
|View full text |Cite
|
Sign up to set email alerts
|

Tumour cell identification by means of Raman spectroscopy in combination with optical traps and microfluidic environments

Abstract: Raman spectroscopy has been recognized to be a powerful tool for label-free discrimination of cells. Sampling methods are under development to utilize the unique capabilities to identify cells in body fluids such as saliva, urine or blood. The current study applied optical traps in combination with Raman spectroscopy to acquire spectra of single cells in microfluidic glass channels. Optical traps were realized by two 1070 nm single mode fibre lasers. Microflows were controlled by a syringe pump system. A novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
143
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(152 citation statements)
references
References 34 publications
1
143
0
4
Order By: Relevance
“…Already, pioneer studies have demonstrated the potential of Raman spectroscopy for in vivo cancer demarcation that can guide surgical procedures or for cell sorting without contaminating antibodies or fluorophores. 78 We believe that combi-nations of current technology, e.g., microfluidic sample delivery, liquid chromatography, or super-resolved optical approaches will soon be combined with Raman spectroscopy to enable even faster sample analysis or the localization of chemical products at subwavelengthlength scales. Raman spectroscopy has evolved from an exotic technique that only a handful of select research groups were able to perform to an entire research area by itself, enriching and complementing other analytical approaches.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Already, pioneer studies have demonstrated the potential of Raman spectroscopy for in vivo cancer demarcation that can guide surgical procedures or for cell sorting without contaminating antibodies or fluorophores. 78 We believe that combi-nations of current technology, e.g., microfluidic sample delivery, liquid chromatography, or super-resolved optical approaches will soon be combined with Raman spectroscopy to enable even faster sample analysis or the localization of chemical products at subwavelengthlength scales. Raman spectroscopy has evolved from an exotic technique that only a handful of select research groups were able to perform to an entire research area by itself, enriching and complementing other analytical approaches.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent demonstration of this potential, Duchow et al 78 combined optical trapping with cell sorting in microfluidic channels to discriminate between erythrocytes, leukocytes, acute myeloid leukemia cells, and two types of breast tumor cells, with an overall accuracy of 92.2% by using 785 nm wavelength excitation and a specificity of 94.9%, after switching to the excitation of Raman scattering at 514 nm.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…Preliminary results from a number of laboratories worldwide [15] have indicated that these novel spectral methods can distinguish between normal tissue types, disease types and stages, and even identify the primary tumors from spectral patterns observed in metastatic cells. Furthermore, these techniques can analyze single, unstained and unlabeled cells, and therefore, can be used in the detection of circulating tumor cells [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This method is more labor intensive, but yields in relatively short time hundreds of spectra of selected cellular features that show enormous sensitivity toward many biochemical processes, such as the metabolic activity in live yeast cells [38,39]. For example, this approach has been used very successfully to follow stem cell differentiation [40][41][42], photochemical changes in melanosomes [43] or for the detection of circulating tumor cells in flow cytometry [16,17]. Finally, due to the very high spatial resolution of Ra-SCP, spectral information from individual bacterial cells can be collected [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some single-cell identification studies have reported the discrimination of different types of cells. For example, in combination with statistical methods, Raman microscopy has been successfully applied to distinguish between benign and malignant cells [18][19][20], and healthy cells and dying or stressed cells [21]; it has also been used to discriminate between cell types [22][23][24][25], even for highly similar cancer cell lines. However, most previous studies focused on distinguishing between different types of cells such as cancer cells and healthy cells, or different states of the same cells.…”
mentioning
confidence: 99%